2022
DOI: 10.1073/pnas.2214344119
|View full text |Cite
|
Sign up to set email alerts
|

Generation of genome-edited chicken and duck lines by adenovirus-mediated in vivo genome editing

Abstract: Conventional avian genome editing is mediated by isolation, culture, and genome editing of primordial germ cells (PGCs); screening and propagating the genome-edited PGCs; and transplantation of the PGCs into recipient embryos. The PGC-mediated procedures, however, are technically difficult, and therefore, the conventional method has previously been utilized only in chickens. Here, we generated germline mosaic founder chicken and duck lines without the PGC-mediated procedures by injecting an adenovirus containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The germline transmission efficiency varies from 4% to 45%; however, the frequency is comparatively higher than those of other retroviral systems. Recently, adenovirus-mediated CRISPR/Cas9 genome editing in chicken blastoderm PGCs produced genome-edited offspring with 11% germline transmission efficiency [ 35 ].…”
Section: Historical Overview Of Genome Modification Strategies For Av...mentioning
confidence: 99%
See 1 more Smart Citation
“…The germline transmission efficiency varies from 4% to 45%; however, the frequency is comparatively higher than those of other retroviral systems. Recently, adenovirus-mediated CRISPR/Cas9 genome editing in chicken blastoderm PGCs produced genome-edited offspring with 11% germline transmission efficiency [ 35 ].…”
Section: Historical Overview Of Genome Modification Strategies For Av...mentioning
confidence: 99%
“…In addition, an adenovirus containing CRISPR/Cas9 targeting for melanophilin ( MLPH ) gene was injected into the quail blastoderm to produce transgenic quail with 45% germline chimera production efficiency and 2.4% to 10% germline transmission efficiency [ 42 ]. Similarly, adenovirus containing CRISPR/Cas9 was injected into duck blastoderms, producing genome-edited progenies with 2% (duck) germline efficiency [ 35 ]. Despite these successful cases, viral systems are difficult to regard as an effective method owing to the variation in transgenic production efficiency and the limited precision of gene editing.…”
Section: Historical Overview Of Genome Modification Strategies For Av...mentioning
confidence: 99%
“…The effects of the adenoviral transduction of the CRISPR/Cas9 system into local tissue were also demonstrated in chick leg muscle [ 46 ]. More recently, genome-edited ducklings were successfully produced by an adenoviral infection into blastoderms, indicating the efficacy of genome editing technology with adenoviruses in poultry and water birds other than chickens and quails [ 47 ]. Previous studies also confirmed the transduction potential of adenovirus type 5 in chicken, quail, and turkey cells [ 48 , 49 ].…”
Section: Current Approaches For Avian Genome Editing Based On the Cri...mentioning
confidence: 99%
“…For instance, virus isolation and culture, which serve as the gold standard for detecting virus infection, involve a complex operation and take 1−2 weeks to confirm culture results. 10 PCR and ELISA can identify pathogens within a few hours with a detection time of several hours. Nevertheless, these techniques are labor-intensive, require professional operators, and expensive testing instruments, making them unsuitable for point-of-care-testing (POCT).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, these methods often have their limitations. For instance, virus isolation and culture, which serve as the gold standard for detecting virus infection, involve a complex operation and take 1–2 weeks to confirm culture results . PCR and ELISA can identify pathogens within a few hours with a detection time of several hours.…”
Section: Introductionmentioning
confidence: 99%